INVESTIGATING THE RELATION BETWEEN ORGANIZATIONAL CLIMATE AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR IN THE PHYSICAL EDUCATION OFFICES EMPLOYEES IN MAZANDARAN PROVINCE - Ahmadizadeh Zahra; Hefzollesan Mehrdad; Ghalehgir Sohrab; Yadollahzadeh Robab; Heydarinezhad Sedighe (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose : The aim of present study was to investigate the relation between organizational atmosphere and organizational citizenship behavior of Mazandaran province physical education offices staff. Material : This is a correlation and descriptive study, and also a field study. Statistical population of the study was the whole staff of Mazandaran province offices of physical education in 1390 (N=188), that 127 of them were selected randomly and with allocating coordination method. Tools for collecting data were three questionnaires, (1) individual characteristics questionnaire, (2) organizational citizenship behavior questionnaire of Bell and Mangog, and (3) organizational climate questionnaire of Sussman & Deep. To analyze data we used descriptive and inferential statistics (Pearson correlation coefficient and multi-variable regression). Results : Study results showed a significant positive relation between organizational climate and its factors with staff organizational citizenship behavior (p≤0/01). Also step-by-step multi-variable regression analyze showed that goal and communication factors are good predictors of organizational citizenship behavior of physical education headquarters staff, respectively (p≤0/01). Conclusions : According to results we recommend that sport organizations managers through creating positive organizational atmosphere, goal clarity and more staff interactions, can increase the outbreak of organizational citizenship behavior in staff, and finally improve organizational efficiency and effectiveness.